The paradox of utilitarian recognition of prior learning: the cases of Portugal and Slovenia - Guimarães, Paula (2021)
In this article, we examine the vertical influence of the European Union (EU) policy on recognition of prior learning (RPL) in one Southern European country (Portugal) and in a Central European one (Slovenia). We stress the influence of the EU policy on adult education (AE) policies and the development of RPL granting professional qualification. Although not widely acknowledged in adult education theoretical discussions, we use the RPL models introduced by Judy Harris to debate the main aims of core official RPL national policy documents from 2000 to 2018 using documentary analysis. Comparative analysis of the two countries is made, and similarities and differences between the RPL provisions are debated. Our findings indicate the relevance of the utilitarian approach to RPL within national policies. Furthermore, these findings allow us to question why employers give little attention to adult learners’ qualification acquired through RPL.